2019
DOI: 10.1371/journal.pone.0225926
|View full text |Cite
|
Sign up to set email alerts
|

Selection of appropriate reference genes for quantitative real-time reverse transcription PCR in Betula platyphylla under salt and osmotic stress conditions

Abstract: Selecting appropriate reference genes is vital to normalize gene expression analysis in birch (Betula platyphylla) under different abiotic stress conditions using quantitative realtime reverse transcription PCR (qRT-PCR). In this study, 11 candidate birch reference genes (ACT, TUA, TUB, TEF, 18S rRNA, EF1α, GAPDH, UBC, YLS8, SAND, and CDPK) were selected to evaluate the stability of their expression in different tissues and under different abiotic stress conditions. Three statistical algorithms (GeNorm, NormFi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…No previous research has shown that TIP41 is the most stable RG under heat stress. ACT2 is a traditional housekeeping gene widely used in many species, such as Betula platyphylla under salt stress and Panicum virgatum L. leaves and roots [58,59]. In this study, ACT2 was an appropriate RG under heat stress, consistent with results from P. praeruptorum under heat stress [54].…”
Section: Discussionsupporting
confidence: 84%
“…No previous research has shown that TIP41 is the most stable RG under heat stress. ACT2 is a traditional housekeeping gene widely used in many species, such as Betula platyphylla under salt stress and Panicum virgatum L. leaves and roots [58,59]. In this study, ACT2 was an appropriate RG under heat stress, consistent with results from P. praeruptorum under heat stress [54].…”
Section: Discussionsupporting
confidence: 84%
“…) have always been very popular. However, these genes have defects, and their expression varies greatly in different tissues, different developmental stages, and different experimental conditions (Chapman and Waldenström, 2015;Li et al, 2019). This is mainly related to the variability of reference genes in different environments and species.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative determination of expression levels of major gene through qRT-PCR is an important method to understand gene function and reveal the response mechanism of plants under adversities [ 21 , 22 ]. The accuracy of qRT-PCR is measured based on the choice of appropriate reference genes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%